2012
DOI: 10.1186/1471-230x-12-52
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Vomiting Syndrome (CVS): is there a difference based on onset of symptoms - pediatric versus adult?

Abstract: BackgroundCyclic Vomiting Syndrome (CVS) is a well-recognized functional gastrointestinal disorder in children but its presentation is poorly understood in adults. Genetic differences in pediatric-onset (presentation before age 18) and adult-onset CVS have been reported recently but their clinical features and possible differences in response to therapy have not been well studied.MethodsThis was a retrospective review of 101 CVS patients seen at the Medical College of Wisconsin between 2006 and 2008. Rome III … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
88
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(93 citation statements)
references
References 24 publications
(31 reference statements)
4
88
1
Order By: Relevance
“…In our study, the response rate for topiramate was 94%. Our results were inconsistent with the findings of Kumar et al 17 .…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…In our study, the response rate for topiramate was 94%. Our results were inconsistent with the findings of Kumar et al 17 .…”
Section: Discussioncontrasting
confidence: 57%
“…The most frequently reported adverse effects related to propranolol or topiramate included restlessness, sleep disturbance, asthenia, dizziness, somnolence, ataxia, tremors, dysarthria, blurred vision, gastrointestinal symptoms, and weight loss. 16,17,22 In the present study, the most commonly observed side effects in both groups included drowsiness, nervousness and dizziness. Weight loss due to appetite decrease is a frequent side effect of topiramate.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Cyclic vomiting syndrome symptoms and frequent use of medical services cause social and work-related issues. For instance, 29%-57% report losing their jobs and 32% are completely disabled by the time they are diagnosed ( Fleisher et al, 2005 ;Kumar et al, 2012 ). Those who are still employed (55%) report missing as many as 20 work days per year ( Fleisher et al, 2005 ).…”
Section: Methodsmentioning
confidence: 96%
“…Lying in a dark, quiet room, and using cold packs have been reported as beneficial strategies to alleviate symptoms and to promote sleep ( Fleisher et al, 2005 ;Lee et al, 2012 ). Individualized treatment for CVS is based on the phase of illness, effectiveness of medications, and the ability to tolerate side effects ( Boles, 2011 ;Boles et al, 2010 ;Fleisher et al, 2005 ;Kumar et al, 2012 ;Namin et al, 2007 ) (see Table 1 ).…”
mentioning
confidence: 98%